2020
DOI: 10.1001/jamanetworkopen.2020.7566
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TP53 Clonal Variants in Papanicolaou Test Samples Collected up to 6 Years Prior to High-Grade Serous Epithelial Ovarian Cancer Diagnosis

Abstract: IMPORTANCE The low 5-year survival rate of women with high-grade serous epithelial ovarian cancer (HGS-EOC) is related to its late diagnosis; thus, improvement in diagnosis constitutes a crucial step to increase the curability of this disease. OBJECTIVE To determine whether the presence of the clonal pathogenic TP53 variant detected in matched primary tumor biopsies can be identified in DNA purified from Papanicolaou test samples collected from women with HGS-EOC years before the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…It has been hypothesized that progression from p53 signature to STIC requires 20 years and another 6 years are needed from STIC to high-grade serous ovarian cancer 7 15 16. In support of this hypothesis, we recently demonstrated that the same p53 mutations found in high-grade serous ovarian cancer biopsies are present in vaginal swabs taken up to 6 years before the diagnosis of high-grade serous ovarian cancer 17. These observations, taken together, suggest that the occurrence of a p53 signature is a common event in the life of every woman, regardless of BRCA mutational status and not all p53 signatures necessarily lead to the development of high-grade serous ovarian cancer.…”
Section: Discussionsupporting
confidence: 67%
“…It has been hypothesized that progression from p53 signature to STIC requires 20 years and another 6 years are needed from STIC to high-grade serous ovarian cancer 7 15 16. In support of this hypothesis, we recently demonstrated that the same p53 mutations found in high-grade serous ovarian cancer biopsies are present in vaginal swabs taken up to 6 years before the diagnosis of high-grade serous ovarian cancer 17. These observations, taken together, suggest that the occurrence of a p53 signature is a common event in the life of every woman, regardless of BRCA mutational status and not all p53 signatures necessarily lead to the development of high-grade serous ovarian cancer.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study by Paracchini at el. (36) provides further evidence that mutated TP53 variants can be detected in Pap smears up to six years prior HGSC diagnosis. Their work focused exclusively on detection of mutated variants of TP53, in a rather small cohort of 17 patients.…”
Section: Dna Mutations In Cervical Cell Swabs In Early Detection Of Ocmentioning
confidence: 61%
“…This proportion was higher (ca. 60%) in some studies focused only on detection of TP53 alterations in HGSC (35,36). This can be partly explained by cancer cells either not being present in the location where the sample is being collected or not present in sufficient amounts.…”
Section: Early Oc Diagnosis -New Strategies and Ideas For Improvementmentioning
confidence: 99%
“…1). Cases enrolled in group B were used to validate, through analysis of clonal pathogenic TP53 somatic variants, the previous findings that shedding of tumor cells from fimbriae to the uterine cavity is a continual and common event in cases who progress toward HGSOC ( 18 ). The median age at diagnosis was 60 and 61 years for groups A and B, respectively (range, 40 to 81 years for group A, and 42 to 80 for group B).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reproduced similar findings on panels of 18 ( 13 ) or 8 genes ( 14 ), further corroborating the evidence that DNA from ovarian cancer cells can be detected in cervical smears. Further studies focused on TP53 mutations common in HGSOC ( 15 18 ). By using ultrasensitive methods, the same tumor TP53 mutations were found in endocervical swabs in more than 60% of cases and up to 80% in the lavage of the uterine cavity ( 19 ).…”
Section: Introductionmentioning
confidence: 99%